A TANTANGAN YANG DIHADAPI DALAM PROSES PEMBELAJARAN OLEH GURU PAUD SELAMA PANDEMI COVID-19: TANTANGAN YANG DIHADAPI DALAM PROSES PEMBELAJARAN OLEH GURU PAUD SELAMA PANDEMI COVID-19 - Brantasari, Mahkamah (Teacher Training and Education Faculty, of Widya Gama Mahakam Samarinda University, 2021)
The Covid-19 incident gave rise to many alternatives and creativity in the community in overcoming the problems it faced, one of which was in the world of education, so far education in carrying out the learning process has mostly used classical methods by using a direct learning system in the classroom, which was attended by students. -student. With the Covid-19 outbreak, the world of education at various age levels from early childhood to higher education must implement an e-learning learning system or what is often referred to as online learning. However, offline learning is also carried out to anticipate misunderstandings and misunderstandings experienced by students, especially in early childhood education, understanding offline learning itself can be interpreted as media that is not equipped with an internet network that can be used by users. Online and offline learning is carried out in early childhood education. The implementation of online and offline learning in early childhood requires creative skills in making learning media using various applications, so that early childhood students do not feel bored in the process of implementing learning. From the learning process that has been carried out at Early Childhood Education both offline and online until now it can still be carried out properly. The teacher tries his best so that the learning process can be carried out correctly, fun, understood and the learning objectives can be carried out to completion.